Computer-aided discovery of phenylpyrazole based amides as potent S6K1 inhibitors. Issue 5 (30th April 2020) - Yin, Yan; Sun, Yuxing; Zhao, Lianhua; Pan, Jinpeng; Feng, Yangbo
Abstract : Ribosomal protein S6 kinase beta-1 (S6K1) is an attractive therapeutic target. Abstract : Ribosomal protein S6 kinase beta-1 (S6K1) is an attractive therapeutic target. In this study, computational analysis of five thiophene urea-based S6K1 inhibitors was performed. Molecular docking showed that the five compounds formed hydrogen bonds with residues Glu173 and Leu175 of S6K1 and hydrophobic interactions with residues Val105, Leu97 and Met225, and these interactions were key elements for the inhibitory potency of the compounds. Binding free energy (Δ G bind ) decomposition analysis showed that Leu97, Glu173, Val 105, Leu175, Leu97 and Met225 contribute the most to Δ G bind . Based on the computer results, phenylpyrazole based amides (D1–D3 ) were designed and synthesized. Biological evaluation revealed that D2 exhibited 15.9 nM S6K1 inhibition, medium microsomal stability and desirable bioavailability.